Improving Students' Speaking Skill Using Role Play Method in English Learning - Novitasari, Novitasari (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2024)
The aim of this research is to evaluate the impact of the role play learning model in improving the speaking skills of Privat Junior High School students in Jember. This research is a follow-up to existing research, with the aim of providing ideas and benchmarks for further research so that it can add to the repertoire of scientific development regarding learning methods that can possibly improve students' speaking abilities. This research adds relevant insight and foundation for improving speaking skills and implementing an effective learning process that emphasizes active participation of students as learning citizens with careful planning and integrity. The results of the research detected that there was a significant increase in students' speaking achievement through the Role Play Method in Class VII Private Junior High Schools in Jember. The application of the role play method to students' speaking skills achievement increases students' speaking accuracy in terms of pronunciation and vocabulary as well as fluency in terms of pauses and hesitations in Class VII students